Religious-scientific Analysis of the Names of God (On the Basis of Azerbaijani Manuscripts) (Part One) - Rahnulla, Yegana (Scholarya Demo Journal of Ruby, 2021)
The names and attributes of Allah, as in all monotheistic religions, are thoroughly studied based on Quranic ayats and hadiths. Under the religious term "asmaul-husna," these attributes of Allah constitute the main branch of various theological fields, particularly the science of discourse (science of kelam). Scholars have different opinions and serious disputes about the divine attributes, a controversial branch of the science of discourse. Summarizing all these ideas, the attributes of Allah are divided into three parts essential names, names related to creation, existence, and the names related to human being, according to the classification of the “Asmaul-husna” of Abu Isa at-Tirmizi, a famous Islamic scholar. This article contains the religious-scientific analysis of the manuscript copies of Sadraddin al-Konavi's work "Sharh asma Allah al-husna", Sadraddin alShirazi's work "Tafsir al-Quran" and the other one named “Sharh asmallah” by an unknown author. These mentioned works that are kept in Azerbaijan contain the names of Allah beginning from Allah to al-Majid. Although the author of “Sharh Asmallah” is not known, it is distinguished by its large volume and extensive interpretation of names among the manuscripts about the beautiful names of Allah. The work “Tafsir al-Quran” Mahammad ash-Shirazi written İn the Institute of Manuscripts named after Mahammad Fuzuli of ANAS. Besides the interpretation of the surahs and ayats of Quran, the interpretation of the hadiths written on various themes is also given in this work. In the interpretation of the hadith on Allah’s beautiful names perfectly presented the lists of the names, their meanings and interpretations. According to Sadraddin al-Konavi's erudite opinion in his work “Sharh Asma Allah al-Husna”, the development of human morality and the attainment of truth is possible through the study of “Asmaul-Husna”. For this reason, the explanation, interpretation and the research of Allah's beautiful names in Sufism widely spread as one of the most important fields.